2021
DOI: 10.37349/emed.2021.00057
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of sleep by smartphone application: comparison with actigraphy and relation to self-reported sleep

Abstract: Aim: Smartphone technology is increasingly used by the public to assess sleep. Specific features of some sleep-tracking applications are comparable to actigraphy in objectively monitoring sleep. The clinical utility of smartphone apps should be investigated further to increase access to convenient means of monitoring sleep. Methods: Smartphone and subjective sleep measures were administered to 29 community-dwelling healthy adults [aged 20-67, Mean (M) = 26.8; 18 women, 11 men], and actigraphy to 19 of them. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the data provided can be used in the treatment and observation processes of sleep disorders. One study [ 53 ] reported sleep assessment results comparing the developed smartphone apps and objective actigraphy data. As a result, there were no significant differences between the methods, except for total sleep time measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data provided can be used in the treatment and observation processes of sleep disorders. One study [ 53 ] reported sleep assessment results comparing the developed smartphone apps and objective actigraphy data. As a result, there were no significant differences between the methods, except for total sleep time measurements.…”
Section: Discussionmentioning
confidence: 99%